Stabilization of the Turkish Economy in the Early 2000s and the Urgent Action Plan - Turkmen, Seref (European Scientific Journal, ESJ, 2023)
This article discusses the stabilisation of the Turkish economy in the early 2000s, with a focus on the Urgent Action Plan (AEP) implemented by the Justice and Development Party (AKP). The AEP aimed to bring about real structural changes in Turkish economic governance, accelerate privatization, provide capital to certain productive sectors, and increase financial discipline, resulting in the radical decline of public debt. The article explores the success of the AEP and the impact of the AKP’s economic policies on the country’s growth, as well as the role of globalization and the European Union in the transformation of the Turkish economy. Finally, the article discusses the political communication surrounding the AEP and the international recognition of Turkey’s economic performance during this period.